2021
DOI: 10.1101/2021.04.07.21255081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of CoronaVac among healthcare workers in the setting of high SARS-CoV-2 Gamma variant transmission in Manaus, Brazil: A test-negative case-control study

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variant P.1 emerged in the city of Manaus in late 2020 during a large resurgence of coronavirus disease (COVID-19), and has spread throughout Brazil. The effectiveness of vaccines in settings with widespread P.1 transmission has not been reported. Methods We performed a matched test-negative case-control study to estimate the effectiveness of an inactivated vaccine, CoronaVac, in healthcare workers (HCWs) in Manaus, where P.1 accounted f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 34 publications
0
47
0
4
Order By: Relevance
“…Argentina, Brazil, Chile, Mexico, and Peru have all agreed to purchase at least 30 million doses of the Chinese CanSino, Sinopharm, and Sinovac (CoronaVac) vaccines, and vaccination with Sinovac and Russia’s Sputnik V are underway in at least six Latin American countries. A study of the CoronaVac vaccine in Manaus, where P.1 is dominant, found it to be 50% effective after a single dose 9. Touchton says governments should obtain permission to manufacture more vaccines locally, even if they are less effective.…”
Section: Vaccines No Panaceamentioning
confidence: 99%
See 1 more Smart Citation
“…Argentina, Brazil, Chile, Mexico, and Peru have all agreed to purchase at least 30 million doses of the Chinese CanSino, Sinopharm, and Sinovac (CoronaVac) vaccines, and vaccination with Sinovac and Russia’s Sputnik V are underway in at least six Latin American countries. A study of the CoronaVac vaccine in Manaus, where P.1 is dominant, found it to be 50% effective after a single dose 9. Touchton says governments should obtain permission to manufacture more vaccines locally, even if they are less effective.…”
Section: Vaccines No Panaceamentioning
confidence: 99%
“…A study of the CoronaVac vaccine in Manaus, where P.1 is dominant, found it to be 50% effective after a single dose. 9 Touchton says governments should obtain permission to manufacture more vaccines locally, even if they are less effective.…”
Section: Vaccines No Panaceamentioning
confidence: 99%
“…It is therefore essential to continue monitoring disease severity across all age groups so vaccination strategies can be adapted rapidly if required. For example, adults seem to retain substantial immunity for at least eight months after vaccination or natural infection,192021 but if ageing immune systems and waning immunity against new variants lead to shorter protection from severe disease, updated vaccines for adults and vaccinating children to reduce transmission may become more desirable. Additionally, emergence of variants with increased severity in children, or in adults with previous immunity, would signal a more urgent need to control both transmission and disease through vaccinating children.…”
Section: Transmissionmentioning
confidence: 99%
“…Notably, the preliminary results of the CoronaVac phase 3 trial in Brazil showed vaccine efficacy of 50•7% (95% CI 35•9 to 62•0%) against symptomatic disease when SARS-CoV-2 lineage P.2 (the zeta variant) was the predominant circulating lineage, 7 and a test-negative case-control study done during a period of SARS-CoV-2 lineage P.1 (gamma variant) dominance estimated vaccine effectiveness at 36•8% (-54•9 to 74•2). 8 The anti-RBD antibody results presented by Tanriover and colleagues 4 were non-quantitative. Although an immune correlate of protection for COVID-19 remains to be determined, absolute antibody titres at multiple timepoints alongside a benchmark of convalescent serum or WHO serum standard would have allowed the comparison of immunogenicity with other vaccine candidates.…”
mentioning
confidence: 96%